End-of-Life Vehicles Initiatives in the Middle East - Harun, Zambri; Almutairi, Yousef; Molla, Altaf Hossain; Sitinjak, Charli; Khashehchi, Morteza; Mohamad, Taib Iskandar; Reda, Eslam (International Journal of Integrated Engineering, 2023)
Many of the governments in the Middle East have overlooked recycling end-of-life vehicles (ELV) for far too long. This is probably because ELV activities are not in line with the governments’ strategic short-term objectives. This research evaluates Gulf Cooperation Council (GCC) countries and selected countries in the Middle East such as Egypt and Iran’s standard operating procedures (SOP) for disposing of the cars and method in keeping unroadworthy-cars off the road. The elements studied here regarding ELV are relevant acts, emission control initiatives, and the disassembly of car procedure. The methods used here are desktop benchmarking and analysis of statistics regarding registered and deregistered cars which include surveys to users and relevant government officials. It is found that generally the governments in the Middle East are lacking in implementing clear directions to ensure sustainable and environmentally friendly ELV as compared with East Asian nations such as Japan, Taiwan and Malaysia. Among the Middle Eastern countries, Qatar provides much more clear directions regarding their ELV methods. The outcome here sheds some light on the entire procedures taken via these nations in managing ELV initiatives and public awareness. This study will benefit the nations as the governments can implement ELV initiatives, as in Europe and East Asian countries.